Comparative analysis of the safety and effectiveness of Nirmatrelvir-Ritonavir and Azvudine in older patients with COVID-19: a retrospective study from a tertiary hospital in China - Shang, Nan; Li, Xianlin; Guo, Zhiyu; Zhang, Lan; Wang, Shanshan (Frontiers in Pharmacology, 2024)
Objective: Numerous studies have explored the treatment outcomes of Nirmatrelvir-Ritonavir and Azvudine in older patients with COVID-19. However, direct comparisons between these two drugs are still relatively limited. This study aims to compare the safety and effectiveness of these two drugs in Chinese older patients with early infection to provide strategies for clinical treatment.Methods: Older COVID-19 patients (age ≥ 65) hospitalized during the winter 2022 epidemic in China were included and divided into Nirmatrelvir-Ritonavir and Azvudine. Demographics, medication information, laboratory parameters, and treatment outcomes were collected. All-cause 28-day mortality, delta cycle threshold (ΔCt), nucleic acid negative conversion time, and incidence of adverse events were defined as outcomes. Propensity score matching (PSM), Kaplan-Meier, Cox proportional hazards model, subgroup analysis, and nomograms were selected to evaluate the outcomes.Results: A total of 1,508 older COVID-19 patients were screened. Based on the inclusion and exclusion criteria, 1,075 patients were eligible for the study. After PSM, the final number of older COVID-19 patients included in the study was 375, and there were no significant differences in demographic characteristics between the two groups (p > 0.05). Compared to the Azvudine group, the Nirmatrelvir-Ritonavir group showed a higher incidence of multiple adverse events (12.8% vs. 5.2%, p = 0.009). The incidence of adverse events related to abnormal renal function was higher in the Nirmatrelvir-Ritonavir group compared to the Azvudine group (13.6% vs. 7.2%, p = 0.045). There were no significant differences between the two groups in terms of all-cause 28-day mortality (HR = 1.020, 95% CI: 0.542-1.921, p = 0.951), whereas there were significant differences in nucleic acid negative conversion time (HR = 1.659, 95% CI: 1.166-2.360, p = 0.005) and ΔCt values (HR = 1.442, 95% CI: 1.084-1.918, p = 0.012).Azvudine and Nirmatrelvir-Ritonavir have comparable effectiveness in reducing mortality risk. Azvudine may perform better in nucleic acid negative conversion time and virus clearance and shows slightly better safety in older patients. Further studies with a larger sample size were needed to validate the result.